Conversion 9-Methyl Octadecene to 1-Octadecanol - Handoko, Donatus Setyawan Purwo (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
The investigations of methyl oleate (methyl 9-octadecenoate) to convert 1-octadecanol, has been done. The conversion was carried out using ZSiA catalysts and fixed bed reactor that was operated at 400, 450, and 500 oC. ZSiA catalyst was prepared by washing zeolite with aquadest, followed by dipping in HCl 2M solution, adding Na2SiO3 5% b/b, dipping in NH4Cl 2M, calcination at 500 oC under nitrogen with flow rate of 20 mL/min for 2 hours, oxydation under oxygen flow rate of 20 mL/min. Characterization of the catalyst included determination of metal content using AAS, acidity using gravimetric method, surface area using Gas Sorption Analyzer NOVA 1000, and crystallinity using XRD. The fixed bed reactor was filled by catalyst and heated up to 400 oC under hydrogen flow rate of 20 mL/min. Then the feed (methyl oleate or methyl 9-octadecenoate) in evaporator was heated up to 400 oC under hydrogen flow rate of 20 mL/min. The reaction product was collected in glass tube and analyzed using GC-MS. Catalytic hydrogenation of methyl oleate produced 87,21% of 1-octadecanol as major product. 1-octadecanol product decreased significantly by the increase of hydrogen flow rate from 20 to 60 mL/min and for 5 to 15 grams catalysts.Keywords: methyl oleate, 1-octadecanol, ZSiA catalysts